Nobody kills himself if he doesn’t want to kill the other - M. M. , Reshetnikov (Advances in Social Sciences Research Journal, 2019)
In this paper, traditional and novel forms of suicidal behavior are analyzed from the perspective of the death drive. Special attention is paid to such phenomena as "death groups" and "suicide terrorism". Previously, suicide was described as a singular act voluntarily and independently committed by an individual, but in the recent decades, hundreds of episodes have occurred in which suicidal individuals killed dozens or even hundreds of innocent people together with themselves. Results of psychoanalytic studies of suicidal behavior are analyzed. Such contemporary societal problems as loss of meaning and perverted ideological attitudes are discussed as an influential cause of increase in aggressive and suicidal behavior.